Anti-war cartoon from New Zealand, 1914 (1914)
1914 1914-1918 "Anti-war cartoon from New Zealand, 1914" [T0256.jpg], 1914 Material issued to dissuade boys from emigrating to Australia and New Zealand where they were liable for military training from the ages of 12 and 14 respectively.